PERANAN KREDIT DALAM MENDORONG KINERJA USAHA KECIL - Nuswantara, Bayu (Kinerja: Jurnal Bisnis dan Ekonomi, 2012)
The objectives of the research were, (1) to analyze the infl uence of credits on small enterprisesperformance, and (2) to formulate the policies for development of credits that can promote the performance ofsmall enterprises. This research used an econometric analysis in the form of simultaneous equation towardsmodels of small enterprises economic consists of eight behavioral equations and three identity relationships.Estimation for structural equation parameters used the method of Two Stage Least Squares (2SLS).The research conclusions are as follows: (1) the credits have an infl uence on the enterprise revenue,which is the main performance indicator of small enterprises, (2) the credits taken by these small enterpriseswill increases with the reduced interest rates, which in turn will increase the enterprise capital, the use of rawmaterials, fuel and labor, and fi nally increase the enterprise revenue, and (3) the policy-making on increasingof credits will provide the greatest impact of the increase in a row on: capital, raw material usage, enterpriseincome, and enterprise revenue. While the combination of policy-making on increasing of credits, increasingof price, and expansion of marketing areas to reach East Java, West Java, Jakarta and surrounding areastogether, will provide the greatest increase in a row on: capital, enterprise income, enterprise revenue, and useof raw materials.Keywords: Credits, small enterprise, enterprise performance, econometric model.